(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Franz Diffusion Cell (FDC) is a widely used in-vitro technique for evaluating drug release and skin permeation from topical and transdermal formulations. It provides a controlled and reproducible system in which the donor and receptor compartments are separated by a suitable membrane, allowing the assessment of drug diffusion across the skin barrier. The present review focuses on the role of advanced analytical techniques in the accurate quantification and evaluation of drug permeation studies performed using Franz diffusion cells. Various analytical methods, including UV–Visible spectrophotometry, High-Performance Liquid Chromatography (HPLC), Ultra-Performance Liquid Chromatography (UPLC), Liquid Chromatography–Mass Spectrometry (LC–MS/MS), Gas Chromatography (GC), and electrochemical techniques, are discussed. These techniques enable accurate determination of important permeation parameters such as cumulative amount permeated, flux, lag time, and permeability coefficient. HPLC and LC–MS/MS offer high specificity, sensitivity, accuracy, and precision, whereas spectroscopic methods provide simple and cost-effective analysis. Proper sample preparation, selection of receptor medium, temperature control, stirring, and maintenance of sink conditions are essential for obtaining reliable results. Recent advances in automation, high-throughput analysis, and real-time monitoring have further improved the efficiency and reproducibility of Franz diffusion cell studies. Overall, the integration of advanced analytical techniques with Franz diffusion cells plays an important role in formulation development, quality control, regulatory evaluation, and research on topical and transdermal drug delivery systems.